Biosorption Method of Removal of Chromium(III) Accumulated with Nasturtium officinale in Water - BASARAN, DAVUT; OPAK-KARA, YESIM (Asian Journal of Chemistry, 2010)
In present studies, Nasturtium officinale was used as a biosorption plant to remove Cr3+ present in water. For these studies, 0.1, 0.3, 0.5, 1.0, 2.0, 3.0, 4.0 and 5.0 ppm solution of Cr3+ has been prepared in water. Nasturtium officinale was immersed in the experimental solutions for 24, 48 and 72 h. The general apperance of the plants have been observed before and after 24, 48 and 72 h. The plants have been analyzed with atomic absorption for measuring the concentration. The initial and final values of concentration of Cr3+ have been found by drawing the calibration lines in UV region. The wet weight has been measured with sensitive balance. The amount of Cr3+ absorption by plant has been calculated with the dependence of the wet weight.